Teaching older workers new tricks: workplace practices and gender training differences in nine European countries - Jelle Lössbroek; Jonas Radl (Ageing & Society, 2019)
Despite its benefits for prolonging careers, participation in training is far lower among older employees (age 50+) than among younger employees. This study analyses gender differences in older employees' training participation. To investigate the predictors of training intensity, we examine two forms of training: formal educational programmes and on-the-job training. The study draws on a novel data-set, the European Sustainable Workforce Survey, carried out in nine European countries in 2015 and 2016, analysing 2,517 older employees and their managers, spread over 228 organisations. We concentrate on the interplay between employees' gender, managers' gender and managers' ageism in shaping older employees' training participation. Our findings indicate comparable training participation of older men and women in both forms of training, yet older women more often pay for enrolment in educational programmes themselves. Also, predictors of training participation are different. In line with the tenet of `gendered ageism', we find that managerial ageism primarily targets older women, excluding female employees from the training opportunities available to their comparable male colleagues. Finally, female managers are associated with higher training participation rates for older employees, but only for older men. This result supports `queen bee' arguments and runs counter to `homophily' arguments. Overall, the study demonstrates that workplace dynamics and managerial decisions contribute to the reproduction of traditional gender divides in the late career.
Keywords: 330; training; gender; ageism; international comparison; older employees